Character Value Depicted In The Character Of “Finding Nemo” - Nelpa Juliana Br Tarigan; Belinda Vista Biru; Yenita Br Sembiring (Peneliti.net, 2022)
This study aims to determine the value of education in the film Finding Nemo. Researcher chose this film because the film Finding Nemo has educational. Value that can shape the character of students and this film can also be reached by all groups. Researcher use the method is qualitative descriptive method will data collection through observation. The result of the study show that the education values contained in the film Finding Nemo can build the character of student through a material lesson plan designed with the educational value found in the film Finding Nemo